The Effects of Environmental Quality on Indonesia's Inbound Tourism - Suharyono, Suharyono; Digdowiseiso, Kumba (International Journal of Energy Economics and Policy, 2020)
In recent years, Indonesia's inbound tourism grew slowly. This study examined the effects of quality of environment on inbound tourism in 32 provinces over the period 2009 – 2018. We utilized several indices of environmental quality such as water quality index (WQI), air quality index (AQI), and environmental quality index (EQI). Meanwhile, our dependent variable, inbound tourism, is measured in terms of incidence and duration of stay. Previous studies acknowledged that there was a potential endogeneity between quality of environment and tourism. Therefore, instrumental variable (IV) in a static panel dataset was carried out in the estimation. The results showed that both WQI and EQI were positively and significantly correlated with the demand for inbound travelers. Furthermore, we found that there was a positive and significant relationship between AQI and length of stay of inbound visitors. Keywords: Environmental Quality; Inbound Tourism; Indonesia. JEL Classifications: Q500, Q530, Z300 DOI: https://doi.org/10.32479/ijeep.10526